Bezpieczeństwo dyskursów w kontekście istniejących interpretacji wydarzeń społeczno-politycznych - Lymar, Andrey (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The dependence of the development of social and political processes on the context of the era and the discourse has long been a subject of research. Crises require every time to pay attention to the quality and content of the texts, which describe these processes. Social institutions have a special responsibility for the development of processes and the impact on young people as a social resource for its development and to exit from the crisis. Article is partly based on previous research and publications by the Author.
Keywords: discourse; political processes; safety; social institutions; social processes; text; youth